Механізм управління діловою активністю підприємства харчової промисловості - Данильчук, Іван Сергійович; Danylchuk, Ivan Serhiyovych (Ірпінь, 2024)
У роботі розкрито теоретико-методичні основи формування механізму управління діловою активністю підприємства харчової промисловості та розробці практичних рекомендацій стосовно удосконалення підходів та інструментарію управління в нинішніх економічних реаліях. За результатами дослідження систематизовано теоретико-методичні підходи до формування механізму управління діловою активністю підприємства, а також запропоновано декілька способів і заходів удосконалення механізму управління діловою активністю підприємства ТОВ «Ковельський хлібокомбінат».

The work reveals the theoretical and methodological foundations of the formation of a mechanism for managing the business activity of a food industry enterprise and the development of practical recommendations regarding the improvement of management approaches and tools in the current economic realities. According to the results of the study, theoretical and methodological approaches to the formation of the business activity management mechanism of the enterprise were systematized, as well as several methods and measures for improving the business activity management mechanism of the Kovelskiy Hlibokombinat LLC were proposed.
Mechanism of management of business activity of a food industry enterprise
Keywords: ділова активність підприємства; управління діловою активністю; механізм; елементи механізму; механізм управління діловою активністю; business activity of the enterprise; business activity management; mechanism; mechanism elements; business activity management mechanism